ISLAMIC PERSPECTIVE ON PANCASILA VALUES IMPLEMENTATION IN HUMAN RIGHTS PRACTICES - Anggraeni, RR Dewi; Ahmad, Pendi (MIZAN: JOURNAL OF ISLAMIC LAW, 2022)
The values contained in Pancasila are real representations of the scope of human rights (HAM) practice. In various views, human rights (HAM) are an absolute thing and need to be upheld for every human being, including in the view of Islam. Pancasila is the ideology of the Indonesian nation that has been agreed upon fairly and cannot be changed just because it follows current developments. This country, which has been contained in Human Rights (HAM) such as equality in the eyes of God Almighty (YME) and human attitudes in respecting other individuals, is an illustration that this country is a state of law. Meanwhile, one of the conditions for running a democracy is the protection of human rights (HAM), which is the main goal of a Pancasila democratic state. This study aims to describe the values of Pancasila in practice in the context of human rights (HAM) and from an Islamic point of view. The method used in this study uses a qualitative method. The results of this study explain that Pancasila is the philosophy of the Indonesian nation. It consists of the essential values for living in Indonesia. Protecting human rights is the goal and condition for democracy to work in Indonesia. Islam and Pancasila are not two contradictory ideas.